Quality Management of Kindergarten Teaching Staff: A Multisite Study of Integrated Islamic Kindergartens in Aceh - Rusydi Ananda; Windisyah Putra; Candra Wijaya (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates teacher quality management in Integrated Islamic Kindergartens in Central Aceh Regency by examining the processes of planning, organizing, implementation, and supervision across Islamic Kindergartens. Methodology: Using a qualitative multisite approach, data were gathered through interviews, observations, and document analysis, and analyzed through systematic data condensation, display, and verification. Main Findings: The findings show that quality planning is guided by a synergy between institutional vision, mission, motto, and objectives with national education standards and JSIT (Jaringan Sekolah Islam Terpadu) guidelines, resulting in a balanced emphasis on academic competence, professional skills, and spiritual formation. Organizational quality is sustained through transparent structures, measurable task distribution, coordinated teamwork, and standardized operating procedures. Recruitment applies competency-based selection enriched with Islamic values, prioritizing Qur’anic mastery, character integrity, pedagogical expertise, and emotional maturity. Teacher development is implemented through Islamic andragogy, integrating professional training with spiritual nurturing via halaqah, mentoring, and routine religious studies. Supervision adopts a holistic model that evaluates academic performance, pedagogical practice, and spiritual consistency to ensure continuous improvement. Novelty/Originality of this study: The novelty of this study lies in the formulation of a hybrid teacher quality management model that fuses national quality assurance frameworks with JSIT principles, positioning moral goodness as the foundation, pedagogical quality as the institutional output, and educational excellence as the long-term goal. This model offers a new theoretical framework and practical reference for enhancing teacher quality in faith-based early childhood education institutions.